SPED fiscal in the perspective of accounting professionals of the municipality of Água Boa – MT - da Silva, Adrielle Lorrane Moreira; Dantas , Vilmar Secundina; Pacheco , Ezequiel Nunes (Seven Editora, 2023)
This research deals with the evaluation of the Fiscal SPED from the perspective of accounting professionals in the Municipality of Água Boa - MT. The general objective is to identify the main challenges and benefits encountered from the implementation of the Fiscal SPED, in the perception of accounting professionals of the offices of the municipality of Água Boa - MT. The theoretical approach deals with topics such as digital bookkeeping and the challenges of its implementation, as well as aspects of the advantages and disadvantages of Fiscal SPED. Regarding methodological aspects, it is characterized by a descriptive exploratory study, in which the data are qualitative with the use of a specific questionnaire applied to accounting professionals working in the sending of the Fiscal SPED. The results showed that the Fiscal Sped generated a great impact on the agility and reliability of the information provided, benefits concerning the standardization and rationalization of processes, and consequently a unification of systems. The challenges are the difficulties with clarity in sped legislation and various errors in transmission files, thus pointing to a need for a fiscal shift on the part of the efficient and agile tax authorities in the correction of problems and also a demand for specific training according to the recurrent needs. DOI: https://doi.org/10.56238/devopinterscie-069